1993
DOI: 10.1172/jci116907
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent hyperpolarization caused by bradykinin in human coronary arteries.

Abstract: The present study was designed to determine whether bradykinin induces endothelium-dependent hyperpolarization of vascular smooth muscle in human coronary arteries, and if so, to define the contribution of this hyperpolarization to endothelium-dependent relaxations. The membrane potential of arterial smooth muscle cells (measured by glass microelectrodes) and changes in isometric force were recorded in tissues from six patients undergoing heart transplantation. In the presence of indomethacin and NG-nitro-L-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
1
6

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(136 citation statements)
references
References 33 publications
5
124
1
6
Order By: Relevance
“…In Tyrode solution, ouabain and a decrease in [Na+le had much less effect on L-N' nitroarginineresistant relaxation of BCA; this has been also shown in guineapig coronary arteries (Chen & Cheung, 1992), rat mesenteric arteries (Ayotunde et al, 1991) and human coronary arteries (Nakashima et al, 1993). Since the inhibitory properties of ouabain and a reduced [Nal]e critically depend on the solutions used, the effect observed with PBS is more likely due to some depolarizing effect of ouabain and reduced [Nal]e rather than interference with EDHF directly.…”
Section: Concmentioning
confidence: 69%
“…In Tyrode solution, ouabain and a decrease in [Na+le had much less effect on L-N' nitroarginineresistant relaxation of BCA; this has been also shown in guineapig coronary arteries (Chen & Cheung, 1992), rat mesenteric arteries (Ayotunde et al, 1991) and human coronary arteries (Nakashima et al, 1993). Since the inhibitory properties of ouabain and a reduced [Nal]e critically depend on the solutions used, the effect observed with PBS is more likely due to some depolarizing effect of ouabain and reduced [Nal]e rather than interference with EDHF directly.…”
Section: Concmentioning
confidence: 69%
“…[39][40][41][42] Although few studies have investigated the role of EDHF in human hypertension, Taddei et al 41 have reported that EDHF partially compensates for the loss of NO to sustain endothelium-dependent vasodilation in patients with essential hypertension. With regard to salt-sensitive hypertensive patients, several studies have reported that impairment of the NO pathway is associated with endothelial dysfunction; 43,44 however, the role of EDHF in endothelial function in salt-sensitive hypertensive individuals remains unresolved and thus warrants further investigation.…”
Section: Upregulation Of Edhf In Salt-induced Hypertension K Goto Et Almentioning
confidence: 99%
“…Although endothelium-dependent hyperpolarization has been demonstrated in bovine, porcine and human epicardial coronary arteries in vitro Nakashima et al, 1993) the chemical nature of this factor is still unclear. Moreover, the role of EDHF in the coronary microcirculation remains to be established.…”
Section: Introductionmentioning
confidence: 99%